Measuring corporate social responsibility towards employees - Anna Remišová; Zuzana Búciová (Journal for East European Management Studies, 2012)
The paper presents a new methodology for measuring a corporate social responsibility (CSR) level based on the Integrative model of CSR. According to the model, which reflects European theoretical fundamentals of CSR, a company cannot be viewed as socially responsible if it does not accept at least basic responsibilities towards all its stakeholders. The main aim of the paper is to present the methodology of determining the CSR basis towards one selected stakeholder - employees, and to provide a set of indicators for measuring a CSR level towards them. The functionality of the indicators was tested in empirical research and proved to be applicable. The paper can be viewed as a guideline to define a CSR basis towards other stakeholders by analogy. – – Der Artikel veranschaulicht eine neue Methodik zur Messung des gesellschaftlich sozialen Verantwortung (CSR)-Levels, basierend auf dem integrativen Modell von CSR. Nach dem Modell, welches die europäischtheoretische Grundlagen von CSR widerspiegelt, kann ein Unternehmen nicht als sozial-verantwortlich angesehen werden, wenn es nicht zumindest eine grundlegende Verantwortung gegenüber allen Interessengruppen akzeptiert. Das wichtigste Ziel dieses Artikels ist es, die Methodik zur Bestimmung der CSR-Grundlagen anhand einer ausgewählten Interessengruppe - den Mitarbeitern - zu präsentieren, und eine Reihe von Indikatoren zur Messung einer CSR-Grundlage bereitzustellen. Die Funktionalität dieser Indikatoren wurde in einer empirischen Forschung getestet und erwies sich als zutreffend. Der Artikel kann als Leitlinie angesehen werden um CSR gegenüber den anderen Interessengruppen in Analogie zu definieren.
Keywords: 650; corporate social responsibility (CSR); the integrative model of CSR; the CSR basis; stakeholder theory; business ethics